The Effect of Inflation, Interest Rates, Exchange Rates, and Real GDP on Financial Deepening in Indonesia: Evidence from Error Correction Model Approach - Devi Putri; Devi Valeriani; Anggraeni Yunita (Department of Development Economics, Universitas Sriwijaya, 2021)
Financial deepening is a benchmark for seeing the role of financial services in the economy, as measured by the ratio between the money supply (M2) and Gross Domestic Product (GDP). This study aims to determine and analyze the effect of inflation, interest rates, exchange rates, and real GDP on financial deepening in Indonesia in the long and short term. The type of research used is quantitative. Sources of data used in this study are secondary data sources obtained from Bank Indonesia (BI) and the Central Bureau of Statistics (BPS). Data analysis using the Error Correction Model (ECM) method. The results show that in the long run, inflation is negatively and insignificantly effect to financial deepening, interest rates are negatively and significantly effect to financial deepening, while the exchange rates and real GDP have a positive and significant effect to financial deepening in Indonesia. Meanwhile, in the short term, inflation is negatively and insignificantly effect to financial deepening, interest rates are negatively and insignificantly effect to financial deepening, exchange rates are positively and insignificantly effect to financial deepening, while real GDP has a positive and significant effect to financial deepening in Indonesia.